Popliteal Artery Injury: Short Term Outcome With or Without Skeletal Trauma - Khan, Md Saifullah; Alam, Sanurul; Ahmed, Nasir Uddin (University Heart Journal, 2012)
Short term outcome of popliteal artery injury with or without skeletal trauma was studied during the period from January 2005 to December 2005, in the department of cardiovascular surgery, National Institute of Cardiovascular Diseases, Dhaka, Bangladesh. Thirty patients undergoing surgical management for popliteal artery injury were divided equally into two groups, 15 patients with skeletal trauma (Group A) and 15 patients without skeletal trauma (Group B). Study shows that seven patients had postoperative complications in entire group, 6 in group A and one in group B. Postoperative infection was the most common complication (16.7% of total patients) in both groups accounting for 4 (26.6% within group) patients in group A and in one patient (6.7% within group) in group B respectively. Limb amputation is the most important parameter of outcome, which was needed in two patients (13.3% within group) of group A and in none of group B. Other complications were thrombosis, neurological deficit and absent distal pulse, all of which occurred exclusively in group A. DOI: http://dx.doi.org/10.3329/uhj.v7i1.10204 UHJ 2011; 7(1): 16-18